Thermostable Cyclodextrin Glucanotransferases (Biological Sciences - PJSIR, 2006)
Hyperthermophilic microorganisms have developed a variety of molecular strategies in order to survive extremely harsh temperatures like 110 °C. For the utilization of natural polymeric substrates, such as starch, they produce special enzymes. The present review focuses on thermostable cyclodextrin glucanotransferases (CGTases; EC 2.4.1.19), which are responsible for the production of cyclodextrins. Only a limited number of thermostable CGTases have been characterized as yet. The thermostable enzymes characterized so far contain all the four conserved regions found in the family-13 of starch-degrading enzymes. The five domains specific for CGTases (A to E) have been identified in these enzymes and the effects of C-terminal truncation of thermostable CGTases have been analyzed. Furthermore, results of the construction of a chimeric enzyme have been included and practical advantages of thermostable enzymes are dis- cussed.